<span>Simplifying
2(10 + -13x) = -34x + 60
(10 * 2 + -13x * 2) = -34x + 60
(20 + -26x) = -34x + 60
Reorder the terms:
20 + -26x = 60 + -34x
Solving
20 + -26x = 60 + -34x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '34x' to each side of the equation.
20 + -26x + 34x = 60 + -34x + 34x
Combine like terms: -26x + 34x = 8x
20 + 8x = 60 + -34x + 34x
Combine like terms: -34x + 34x = 0
20 + 8x = 60 + 0
20 + 8x = 60
Add '-20' to each side of the equation.
20 + -20 + 8x = 60 + -20
Combine like terms: 20 + -20 = 0
0 + 8x = 60 + -20
8x = 60 + -20
Combine like terms: 60 + -20 = 40
8x = 40
Divide each side by '8'.
x = 5
Simplifying
x = 5</span>
No because In the relation , y is a function of x, because for each input x (1, 2, 3, or 0), there is only one output y. x is not a function of y,
(0,a)
it didnt move left or right on the x-axis
it went up a units (since its half of 2a)
Answer:
A positive 15
Step-by-step explanation:
The key word earn tells us he's gaining.
Answer:
10
Step-by-step explanation:
HCF of 20, 40 & 50:
20: 1, 2, 4, 5, 10, 20
40: 1, 2, 4, 5, 8, 10, 20, 40
50: 1, 2, 5, 10, 25, 50
HCF: 10
Topic: HCF and LCM
If you like to venture further, feel free to check out my insta (learntionary). I'll be constantly posting math tips and notes! Thanks!